2017
DOI: 10.1097/bpo.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

The Declining Incidence of Legg-Calve-Perthes’ Disease in Northern Ireland: An Epidemiological Study

Abstract: Level IV-retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…During this time, the proportion of LCPD versus all pediatric surgical admissions also declined by 52%. This trend appears to be similar to the declining LCPD incidence reported in other countries 5,16…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During this time, the proportion of LCPD versus all pediatric surgical admissions also declined by 52%. This trend appears to be similar to the declining LCPD incidence reported in other countries 5,16…”
Section: Discussionsupporting
confidence: 87%
“…This trend appears to be similar to the declining LCPD incidence reported in other countries. 5,16 The racial diversity of the LCPD cohort did not change across the study period, there was a maintained white predominance. During this same time, however, there was an increase in the diversity of the US child population.…”
Section: Discussionmentioning
confidence: 97%
“…The heterogeneous prevalence reported opens the discussion for the examination of possible environmental and social factors involved in the aetiology of the disease[1-3,29]. In support of this, three studies[21,26,87] reported a possible association between the decrease in the incidence and lifestyle changes over recent years, exposure to environmental risk factors like smoking, delayed epiphyseal ossification, low birthweight, child deprivation and obesity. However, the results are not definitive.…”
Section: Discussionmentioning
confidence: 92%
“…Although juvenile osteochodrosis of the femoral head (Legg-Calvé-Perthes disease) and avascular bone necrosis have been studied extensively for at least 100 years there are still controversies in etiology of the disease and optimal treatment of the condition [1][2][3][4][5][6][7][8]. Changes in the femoral head in Legg-Calvé-Perthes disease and avascular necrosis evaluated with imaging modalities (MSCT, MRI, uS) are well described at different stages of the disease [9][10][11].…”
mentioning
confidence: 99%